PENGEMBANGAN ANALISIS KEBUTUHAN DAN ANALISIS SITUASI KURIKULUM PEMBELAJARAN BAHASA - Irfadila, Mimi Sri (FKIP UMSB, 2025)
This study aims to develop a needs analysis and situation analysis model integrated into language learning curriculum planning. In the context of 21st century education, language learning curriculum is required to be adaptive to the needs of learners, socio-cultural developments, and dynamic literacy competency demands. Therefore, needs and situation analysis are very important initial components in designing a relevant and applicable curriculum. This study uses a descriptive-qualitative approach with data collection techniques in the form of document studies, interviews, and questionnaires involving teachers, students, and education stakeholders. The results of the study indicate that accurate student needs analysis, combined with contextual situation mapping (institutional, sociocultural, and policy), can provide a strong foundation in designing learning outcomes, materials, and learning strategies that are more contextual and responsive. This study recommends the development of practical instruments and guidelines that can be used by curriculum developers and language teachers in compiling a curriculum based on real field needs.